Model for determination of a power transmission system frequency response : doctoral thesis - Levačić, Goran (G. Levačić ; Fakultet elektrotehnike i računarstva, 2018)
In this work a custom mathematical model of three-phase transmission network for calculations in the frequency-domain in EMTP-type software is developed. With the possibility of analysis of resonant frequencies and power transmission network frequency response, it can be used as well for steady-state and time-domain calculations. Developed model in EMTP-RV is validated by comparison of load-flow results with the model which primary focus is load-flow calculations, e.g. PSS/E. Frequency dependent network equivalent seen from the certain point of the network can be very useful in cases of new power plant connection, because they can be transmitted by TSOs to power plant owners or manufacturers to perform certain type of calculations. Model of frequency dependent network equivalent obtained using the Vector Fitting method is validated through comparison of time-domain results with full-network model and with on-site measurements. A case scenario of power plant connection with long HVAC cable is analyzed on developed model to show its influence on network’s frequency response and resonant frequencies. Also, a procedure for identification of areas sensitive to the change of network topology is established. In order to determine the most influential parameters of the power transmission network on frequency response, a procedure for sensitivity analysis which consists of defining an input parameters and output signals and their parameterizing with EMTP-type module for parametric studies is established. Sensitivity analysis is performed graphically and using Moriss Method. Key words: EMTP-RV, power transmission network, resonance phenomenon, resonant frequencies, frequency response, frequency dependent network equivalent, long cables, PSS/E, sensitive network areas, sensitivity analysis, Moriss’ Method.